Perceived Impact of COVID-19 on Students' Academic Performance in Colleges of Education in Ghana - Adzaku, Sally; Agbleze, Henry; Afutor, Philemon (African Journal of Education and Practice, 2022)
Purpose: This study investigated the perceived impact of COVID-19 on students' academic performance in Colleges of Education in Ghana. Methodology: Descriptive survey design was adopted for the study. A sample of 346 students was selected from a population of 3,500 students in three selected Colleges of Education in the Volta Region of Ghana using convenience sampling procedure. Data were gathered using questionnaire and analysed using means and standard deviation. Data were presented in tables after the analysis. Findings: The study found that students found it difficult to focus during online lessons and that their academic performance had worsened due to the COVID-19 pandemic. In terms of the challenges encountered by students during the COVID-19 Pandemic, the study revealed that poor internet connectivity, lack of needed resources like laptops to access online learning system and lack of conducive learning atmosphere in the house were identified. From the results, it was concluded that the COVID-19 Pandemic at its peak has been detrimental to the academic performance of students in Colleges of Education in Ghana. Unique Contribution to Theory, Practice and Policy Recommendation: The study highlighted the fact that students can learn not only in-person but can engage in remote learning. This backed the position of the Transactional Distance Theory used in the study. In improving learning in the wake of COVID-19, Colleges of Education should provide platforms for online learning with easy access and usage for students. Generally, policy makers should make policies that would make online learning a part of the education system at all levels of education. This would be a positive adjustment caused by the COVID-19 outbreak.